Koffeinintoxikation in suizidaler Absicht - Uehlein, Sabrina; Schneider, Reinhard; Stahl, Klaus; Dechant, Katharina (Innere Medizin, 2025)
Following oral ingestion of 40 g of caffeine with suicidal intent, a 34-year-old male patient presented with worsening nausea, emesis and polyuria. The patient’s lab results showed lactic acidosis, rhabdomyolysis, hypokalemia and hypernatremia. Symptomatic treatment as well as fluid and electrolyte replacement were initiated. By means of hemodialysis, sufficient elimination of caffeine could be achieved. After stabilization, the patient was transferred to the department of psychiatry and psychotherapy for treatment of his depression.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Emesis; Hemodialysis; Hypokalemia; Lactic acidosis; Polyuria